2008
DOI: 10.1007/s10764-008-9240-2
|View full text |Cite
|
Sign up to set email alerts
|

Acoustical Aspects of the Propagation of Long Calls of Wild Leontopithecus rosalia

Abstract: Golden lion tamarins emit conspicuous and complex long calls. Little is known about the propagation distance of the calls, and the knowledge is important to understand the function of long calls. The high-frequency spectrum of the calls renders them susceptible to substantial degradation inside forest habitats. We investigated 1) the propagation distance of the long call and if the height from the ground affects the degree of degradation and 2) whether long-call acoustic variation affects the propagation dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 58 publications
(72 reference statements)
0
8
0
1
Order By: Relevance
“…This hypothesis may explain why the long calls were also sometimes emitted from the lowest stratum of the forest. Golden lion tamarin long calls have frequencies between 4.0 and 12.00 kHz (HALLOY & KLEIMAN 1994, RUIZ-MIRANDA & KLEIMAN 2002, and degrade rapidly within the lowland forest, especially the second phrase of the call (SABATINI & RUIZ-MIRANDA 2008). The second phrase of the call contains information related to population and sex (BENZ et al 1990, RUIZ-MIRANDA & KLEIMAN 2002.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis may explain why the long calls were also sometimes emitted from the lowest stratum of the forest. Golden lion tamarin long calls have frequencies between 4.0 and 12.00 kHz (HALLOY & KLEIMAN 1994, RUIZ-MIRANDA & KLEIMAN 2002, and degrade rapidly within the lowland forest, especially the second phrase of the call (SABATINI & RUIZ-MIRANDA 2008). The second phrase of the call contains information related to population and sex (BENZ et al 1990, RUIZ-MIRANDA & KLEIMAN 2002.…”
Section: Discussionmentioning
confidence: 99%
“…An experiment using play-backs of natural long calls showed that calls emitted from different heights show differences in total attenuation of the long call at 80 m from the source, the main effect of height on sound degradation being on the syllables of the second phrase. The latter corresponds to the highest frequencies and is also were information on sex and group differences is contained (SABATINI & RUIZ-MIRANDA 2008). These findings suggested that it would be advantageous for golden lion tamarins to consider their position within the forest strata while emitting vocalizations.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Attenuation of signals can contribute to major limitations on communication distance in frogs (e.g., Penna et al 2006Penna et al , 2013, and as has been repeatedly demonstrated for insects (Römer 2012), birds (Slabbekoorn 2004;Brumm and Naguib 2009), and mammals (Waser and Waser 1977;Sabatini and Ruiz-Miranda 2008), its magnitude is influenced by the calling venue. For example, Wells and Schwartz (1982), working with glassfrogs (Hyalinobatrachium fleischmanni), found that call transmission through dense vegetation caused greater excess attenuation than did call transmission at greater height through less obstructed habitat.…”
Section: Introductionmentioning
confidence: 96%
“…These roles require the calls to contain information about an individual, and acoustic analyses of these calls across the primate taxa have shown evidence for both individual [Marler and Hobbet, 1975;Waser, 1977;Zuberbühler et al, 1997;Wich et al, 2003;Sabatini and Ruiz-Miranda, 2008;Price et al, 2009;Erb et al, 2013] and contextual variation [Mitani and Nishida, 1993;Snowdon et al, 1983;Zuberbühler et al, 1997;Wich et al, 2003;da Cunha and Byrne, 2006;Schell and Zuberbühler, 2012;Erb et al, 2013], including those produced by orang-utans (Pongo pygmaeus and Pongo abelii) [Delgado, 2003;Spillmann et al, 2010].…”
Section: Introductionmentioning
confidence: 99%